2013
DOI: 10.1007/s00223-013-9752-4
|View full text |Cite
|
Sign up to set email alerts
|

Control of Bone Remodeling by the Peripheral Sympathetic Nervous System

Abstract: The skeleton is no longer seen as a static, isolated, and mostly structural organ. Over the last two decades, a more complete picture of the multiple functions of the skeleton has emerged, and its interactions with a growing number of apparently unrelated organs have become evident. The skeleton not only reacts to mechanical loading and inflammatory, hormonal, and mineral challenges, but also acts of its own accord by secreting factors controlling the function of other tissues, including the kidney and possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 125 publications
3
102
0
1
Order By: Relevance
“…Accordingly, the bone homeostasis regulated by leptin requires the integrity of the hypothalamus, which in turn affects sympathetic activity [18]. Consequently, the sympathetic nervous system represents an important linkage between the brain and bone [18][19][20][21].…”
Section: Bone Homeostasis Regulated By the Central Nervous Systemmentioning
confidence: 99%
“…Accordingly, the bone homeostasis regulated by leptin requires the integrity of the hypothalamus, which in turn affects sympathetic activity [18]. Consequently, the sympathetic nervous system represents an important linkage between the brain and bone [18][19][20][21].…”
Section: Bone Homeostasis Regulated By the Central Nervous Systemmentioning
confidence: 99%
“…10 Although early studies suggested that such coordination between osteoclast and osteoblast activity occurred in relative isolation in the basic multicellular unit, it is now clear that several important local accessory cell types influence bone metabolism through their paracrine secretions, 11 and may mediate many of the effects of drugs and cytokines on bone metabolism. These accessory cells include osteocytes, 12 bone marrow stromal cells and osteal macrophages; 13 some less well-delineated influences include those from local endothelial cells, 14 nerve cells 15,16 and cell populations of the bone marrow cavity such as lymphocytes, as discussed below.…”
Section: Multiple Cellular Interactions Regulate Bone Structurementioning
confidence: 99%
“…These pathways probably significantly regulate fracture healing. Recently, research based on a number of anatomic, pharmacologic, and genetic studies on β2 β-adrenergic receptor (AR) have shown that the sympathetic nervous system (SNS) can link the central nervous system with the skeleton (Castañeda-Corral et al, 2011;Elefteriou et al, 2014). By regulating the SNS and βAR signaling, the SNS can control bone remodeling (Elefteriou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%